Low density polyethylene degradation by filamentous fungi. (1st April 2021) - Spina, Federica; Tummino, Maria Laura; Poli, Anna; Prigione, Valeria; Ilieva, Viktoria; Cocconcelli, Piersandro; Puglisi, Edoardo; Bracco, Pierangiola; Zanetti, Marco; Varese, Giovanna Cristina
Abstract: Polyethylene (PE) is the most abundant non-degradable plastic waste, posing a constant and serious threat to the whole ecosystem. In the present study, the fungal community of plastic wastes contaminating a landfill soil has been studied. After 6 months of enrichment, 95 fungi were isolated, mostly belonging to the Ascomycota phylum. They were screened under in vitro condition: most of fungi (97%) were capable of growing in the presence of PE powder (5–10 g L −1 ) as sole carbon source. Fusarium strains better tolerated high concentration of PE. Up to 13 strains were chosen for further degradation trails, where the process was monitored by respirometry tests and by observing changes in PE chemical and physical structure by FTIR analysis and SEM images. Major results were observed for Fusarium oxysporum, Fusarium falciforme and Purpureocillum lilacinum, as they caused strong oxidation phenomena and changes in the PE film morphology. Results suggested that the initial oxidation mechanisms targeted first the methyl terminal groups. Changes in the infrared spectra were strongly strain-dependent, denoting the activation of different degradation pathways. Through the SEM analysis, the actual damages provoked by fungi were observed, including swellings, pits and furrows, bumps and partial exfoliations. Considering the rising concern about plastic disposal worldwide, the ability of these fungi to colonize PE and utilize it as carbon source is of great interest, as no pretreatments and pro-oxidant stimulants were needed. Graphical abstract: Image 1 Highlights: Ninety-five fungi were isolated from plastic contaminating a landfill soil. Fusarium, Purpureocillium and Aspergillus spp. were the most abundant fungi. Fusarium strains were the most tolerant to high concentration of PE powder. Three fungi deeply altered PE surface causing the strongest oxidation phenomena. Abstract : The microbial community of a plastic-polluted landfill soil was described. Among the isolated fungi, some of them showed important degradation skills against polyethylene.